Vilaça, Aparecida. Morte na Floresta. 2020. São Paulo: Editora Todavia. 56 p. - Quadros, Caroline Leonardi de (Campos - Revista de Antropologia, 2020)
Resenha do livro Morte na Floresta, de Aparecida Vilaça, publicado em 2020.